Hulvi’nin Gülşen-Raz Lahici Şerhi tercümesi ve değerlendirilmesi - Arefeoğlu, Gökhan (My University, 2005)
H.720/ 1321 tarihinde vefat eden Şeyh Mahmud Şebüsterî büyük bir âlim ve mutasavvifdir. Kendisinden sonra gelen mutasavviflar üzerinde derin tesirler birakmiş ve adindan sik sik bahsettirmiştir. En meşhur eseri olan Gülşen-i Râz yüz yillar boyunca gerek Islâm ülkelerinde gerek Bati dünyasinda okuna gelmiş, son derece açik ve akici üslubu ile günümüze kadar ilim adamlari ve halk arasinda hakli bir şöhret bulmuştur. Tasavvuf usulü ve düşüncesi hakkinda yazilmiş kitaplar arasinda en muteber ve derli toplu risâlelerden biri olan Gülşen-i Râz, hicri 710 Şevvâlinde (1311 Şubat) tarihinde nazm edilmiş olup, Emir Hüseyni adli Horasanli bir şeyhin Tasavvuf düşüncesi ve usulü hakkinda sormuş oldugu on beş soruya Şeyh Mahmud Şebüsterî`nin verdigi cevaplardan oluşmaktadir. Eser özellikle tasavvuf yoluna müntesib sâliklere kilavuz olacak temel kitablardan biri olmuştur. Gülşen-i Râz, tasavvuf nazariyeleri ile sufilerin ilâhi aşkini ve bilhassa sufîlerin mecazlardan kastettikleri mânâlari anlamak bakimindan başta gelen degerli kitablardan biridir. Sadece tasavvufun degil, mümkün ve vâcib, kidem ve hudus gibi kelâm ilminin ve Islâm felsefesinin de konulari Gülşen-i Râz`da açiklanmaktadir. Lâhicî ise Gülşen-i Râz`in en meşhur şarihidir. Mefâhitü`l-İcaz fi Şerh-i Gülşen-i Râz adını taşıyan şerhi, hem zamanında hem de sonraki dönemlerde çok meşhur olmuş defalarca basılmıştır. Kaynakların hemen hepsi Lâhicî şerhinin Gülşen-i Râz şerhleri içersinde Mefâhitü`l İcâzın en mükemmel şerh olduğu konusunda müttefiktir. Câm-ı Dil Nüvâz ise Lâhicî`nin Mefatihü`l-İcâz fi Şerhi Gülşen-i Râz adlı eserinin Mahmud Cemâleddin Hulvî tarafından kısaltılmak suretiyle Osmanlıcaya tercümesidir. Mahmud Cemâleddin Hulvî, o güne kadar ariflerin seyr-u süluk yoluna girenlere yol gösterici olarak pek çok kitap yazdıklarını belirtir. Ona göre her bir beyti engin nitelikler taşıyan Şeyh Mahmud Şebüsterî`nin Gülşen-i Râz adlı eseri diğerlerinden üstündür. Hulvî, bu eserin Şeyh Muhammed Lahicî tarafından yapılan Mefâtihü'l-İ'câz fi Şerh-i Gülşen-i Râz adlı şerhini görüp beğenerek tebyin ve terkîn ile Osmanlıcaya tercüme ettiğini söyler. Biz bu tercümeyi yeni harflere aktararak Osmanlı tasavvuf tarihi çalışmalarına bir nebzede olsa katkımız olduysa bizim için büyük bahtiyarlık olacaktır. Sheik Mahmud Shabustari, who died in 720 A.H./ 1321 A.C., was an eminent scholar and Sufi. He had deep influence on those Sufis that succeeded him, deserving to be oft mentioned. His most noteworthy work, Gulshan Al-Raz (The Rosary of Secrets), which has ever been read not only in Islamic countries but also in the Western world for centuries, has received due commendation among both scholars and the public by virtue of its very clear and fluent style up to our time. Gulshan Al-Raz, one of the most distinguished and well-organized treatises on the manner and thought of Sufism, which was versified in the month of Shawwal, 710 A.H. (February, 1311 A.C.), is composed of Sheik Mahmud Shabustari's replies to the fifteen questions asked by a Sheikh called 'Emir Hussain' from Horasan concerning the manner and thought of Sufism. This very work has become one of the essential books to guide the followers of Sufism. Gulshan Al-Raz is one of the most precious books from the point of reasoning out the theories of Sufism, the divine love of Sufis and the interpretations of Sufis for metaphors. Apart from Sufism, such issues of the Science of Holy Qur'an as Imqan (the Contingent) and Wajib (the Necessary Existence), Qidem (the Eternal Existence) and Hudus (the Emergence) as well as the subjects of Islamic Philosophy have all been explicated in Gulshan Al-Raz. Yet, Lahijih is the most notable annotator of Gulshan Al-Raz. His annotation called Mafahitu'l-Ijaz fi Sharh Al-Gulshan Al-Raz became well-known not only in his era but also in later times and has been printed repeatedly. Almost all the references are unanimous as to that Mafahitu'l-Ijaz is the best of all the interpretations of Gulshan Al-Raz. The book entitled Jam Al-Dil Nuwaz is in fact an abridged Ottoman translation by Mahmud Jamaluddin Hulwi of the work entitled Mafahitu'l-Ijaz fi Sharh Al-Gulshan Al-Raz by Lahiji. Mahmud Jamaluddin stated that Muslim scholars had written a great number of books beforehand to guide those that entered the path of Sayr Al-Suluq (the course of special training of a religious order). According to him, the book named Gulshan Al-Raz authored by Sheik Mahmud Shabustari, each couplet of which bears vast qualities, is superior to the others. Hulwi stated that he had translated this work into Ottoman through explanation and abridgment having been impressed by the annotation called Mafahitu'l-Ijaz fi Sharh Al-Gulshan Al-Raz authored by Sheik Muhammad Lahiji. We should be very much pleased if we have humbly managed to contribute to the studies and researches on the History of Ottoman Sufism by having transliterated this translation into Latin letters.
Keywords: Akâid ve Kelâm; Din; İslam Dini; Tasavvuf